Combination therapy with remote ischaemic conditioning and insulin or exenatide enhances infarct size limitation in pigs. (4th June 2015) - Alburquerque-Béjar, Juan José; Barba, Ignasi; Inserte, Javier; Miró-Casas, Elisabet; Ruiz-Meana, Marisol; Poncelas, Marcos; Vilardosa, Úrsula; Valls-Lacalle, Laura; Rodríguez-Sinovas, Antonio; Garcia-Dorado, David
Abstract: Aims: Remote ischaemic conditioning (RIC) has been shown to reduce myocardial infarct size in patients. Our objective was to investigate whether the combination of RIC with either exenatide or glucose–insulin–potassium (GIK) is more effective than RIC alone. Methods and results: Pigs were submitted to 40 min of coronary occlusion followed by reperfusion, and received (i) no treatment, (ii) one of the following treatments: RIC (5 min ischemia/5 min reperfusion × 4), GIK, or exenatide (at doses reducing infarct size in clinical trials), or (iii) a combination of two of these treatments (RIC + GIK or RIC + exenatide). After 5 min of reperfusion ( n = 4/group), prominent phosphorylation of Akt and endothelial nitric oxide synthase (eNOS) was observed, both in control and reperfused myocardium, in animals receiving GIK, and mitochondria from these hearts showed reduced ADP-stimulated respiration. 1 H NMR-based metabonomics disclosed a shift towards increased glycolysis in GIK and exenatide groups. In contrast, oxidative stress (myocardial nitrotyrosine levels) and eNOS uncoupling were significantly reduced only by RIC. In additional experiments ( n = 7–10/group), ANOVA demonstrated a significant effect of the number of treatments after 2 h of reperfusion on infarct size (triphenyltetrazolium, % of the area at risk; 59.21 ± 3.34, 36.64 ± 3.03, and 21.04 ± 2.38% for none, one, and two treatments, respectively), and significant differences between one and two treatments ( P = 0.004) but not among individual treatments or between RIC + GIK and RIC + exenatide. Conclusions: GIK and exenatide activate cardioprotective pathways different from those of RIC, and have additive effects with RIC on infarct size reduction in pigs.